"My experiences were highly-dependent on the knowledge and enthusiasm of the tutor": graduates' feedback of experiential learning in an MPharm programme Part 1 (TELL Project). (September 2020) - Jacob, Sabrina Anne; Boyter, Anne C
Highlights: Experiential learning plays a key role in preparing pharmacy students for practice Placement experiences were dependent on tutors and placement sites Perceived as extra pair of hands at community pharmacy placements Students appreciative of hospital placement despite lack of hands-on experience Limited placement duration was thought to impede effective learning opportunities Abstract: Pharmacy students undertake experiential learning to prepare them for practice. With the move to more patient-facing roles, there is a need to assess if the experiential learning prepares students for practice. A mixed-methods study was undertaken to obtain the feedback of graduates currently in pre-registration training on their experiential learning experience. There were 63 (response rate 55.8%) responses to the online survey. One focus group consisting of four graduates, and ten one-on-one interviews were conducted. Placement experience was dependent on tutors and placement sites. There was displeasure with community placements as they were relegated to dispensing duties, but satisfaction with their hospital experience despite only being allowed to shadow tutors. The limited duration of placements was highlighted, especially in hospital settings. Tutor training is key to ensuring students have an optimum experience. Sites should be made to see the value of having students, so that they are allowed patient contact.